Dextran sulphate inhibits an association of prions with plasma membrane at the early phase of infection. (October 2021) - Fuse, Takayuki; Nakagaki, Takehiro; Homma, Takujiro; Tange, Hiroya; Yamaguchi, Naohiro; Atarashi, Ryuichiro; Ishibashi, Daisuke; Nishida, Noriyuki
Highlights: The attached PrP Sc localizes into lipid rafts. DS500 inhibits the attachment of PrP Sc to the cell surface. DS500 inhibits 22 L prion transmission in mouse neuroblastoma cells. Abstract: The defining characteristic of prion diseases is conversion of a cellular prion protein (PrP C ) to an abnormal prion protein (PrP Sc ). The exogenous attachment of PrP Sc to the surface of a target cell is critical for infection. However, the initial interaction of PrP Sc with the cell surface is poorly characterized. In the current study, we specifically focused on the association of PrP Sc with cells during the early phase of infection, using an acute infection model. First, we treated mouse neuroblastoma N2a-58 cells with prion strain 22 L-infected brain homogenates and revealed that PrP Sc was associated with membrane fractions within three hours, a short exposure time. These results were also observed in PrP C -deficient hippocampus cell lines. We also demonstrate here that PrP Sc from 22 L-infected brain homogenates was associated with lipid rafts during the early phase of infection. Furthermore, we revealed that DS500, a glycosaminoglycan mimetic, inhibited both the attachment of PrP Sc to membrane fractions and subsequent prion transmission, suggesting that the early association of prions with cell surface is important for prion infection.